Sharia Based Quintuple Bottom Line: Transforming Triple Bottom Line in Islamic Banking - Ana Zahrotun Nihayah Ana; Muchlis Yahya; Ali Murtadho; Lathif Hanafir Rifqi (Universitas Pembangunan Nasional Veteran Jakarta, 2026)
ABSTRACT POJK No. 51/POJK.03/2017 obliges Indonesian banks to implement sustainable finance based on economic, social, and environmental performance. However, for Islamic banking, this Triple Bottom Line (TBL) orientation remains insufficient because it does not explicitly accommodate sharia compliance, spirituality, and intellectual development. This study aims to construct a Sharia-based Quintuple Bottom Line (QBL) model by integrating the five objectives of Maqasid al-Shari’ah with sustainability dimensions. Using a conceptual research design through literature review and theoretical synthesis, the study maps hifz al-mal, hifz al-nafs, hifz al-nasl, hifz al-din, and hifz al-'aql into profit, people, planet, piety, and potential. The findings show that QBL extends TBL by adding piety and potential as two dimensions needed to guide Islamic banks in developing halal, ethical, innovative, and sustainable financing practices. The model offers practical implications for product development, sharia governance, risk management, financial literacy, and green financing in Islamic banking. ABSTRAK POJK No. 51/POJK.03/2017 mewajibkan bank di Indonesia menerapkan keuangan berkelanjutan berbasis kinerja ekonomi, sosial, dan lingkungan. Namun, dalam konteks perbankan sharia, orientasi Triple Bottom Line (TBL) belum memadai karena belum secara eksplisit memasukkan kepatuhan sharia, spiritualitas, dan pengembangan intelektual. Penelitian ini bertujuan menyusun model Quintuple Bottom Line (QBL) berbasis sharia dengan mengintegrasikan lima tujuan Maqasid al-Shari’ah ke dalam dimensi keberlanjutan. Dengan menggunakan desain penelitian konseptual melalui tinjauan pustaka dan sintesis teoritis, studi ini memetakan hifz al-mal, hifz al-nafs, hifz al-nasl, hifz al-din, dan hifz al-'aql ke dalam profit, people, planet, piety, dan potential. Hasil kajian menunjukkan bahwa QBL memperluas TBL dengan menambahkan piety dan potential sebagai dimensi yang diperlukan untuk mendorong praktik pembiayaan bank sharia yang halal, etis, inovatif, dan berkelanjutan. Model ini berimplikasi pada pengembangan produk, tata kelola sharia, manajemen risiko, literasi keuangan, dan pembiayaan hijau.